Single centre experience of ossiculoplasty using different materials: a subjective and objective evaluation - Kumar, Vijay; Bhavana, Kranti; Bharti, Bhartendu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Chronic otitis media has serious impact over the ossicular integrity in middle ear resulting in ossicular necrosis and various grades of hearing loss along with other associated symptoms. Tympanomastoidectomy with ossicular reconstruction using various materials can improve the symptoms. Methods: A retrospective study of 50 patients underwent tympanomastoidectomy with ossiculoplasty in Department of ENT and Head and Neck Surgery at AIIMS Patna from April 2017 to 2018. Patients with chronic otitis media having ossicular necrosis with ABG (air bone gap) more than 25 dB were included in this study. PORP (partial ossicular reconstruction prosthesis) and TORP (total ossicular reconstruction prosthesis) were used as ossicular reconstruction after clearance of disease. This study was expressed as subjective and objective evaluation following ossiculoplasty. Results: Fifty patients having chronic otitis media with decreased hearing and other associating symptoms were included in this study. Preoperative air conduction threshold was 55.32 dB with preoperative ABG was 44.24 dB. Postoperative result was summarised as postoperative AC threshold was 32.72 dB with gain of 22.60 dB with ABG 25.45 dB. Conclusions: Chronic otitis media may lead to ossicular necrosis and various grade of hearing loss. A proper technique and skilled tympanomastoidectomy with ossiculoplasty can improve the symptoms of chronic otitis media.